Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. Strategic leadership and its role in achieving organizational justice in private Yemeni universities from the point of view of academic and administrative leaders Mrs. Fatima Mohammed Maqbool Qaiqab , Co-Prof. Abdulaziz Abdul Hadi Al-Amri 2. The Practicing Degree of Early Elementary Grades’ Teachers for Creative Thinking Skills from Their Point of View Mrs. Mariah Abdullah Alshammari, Dr. Mansour Muzil Alanazi 3. The role of the mother in the scientific formation of her children in the light of Islamic educational thought Imam Malik bin Anas as a model Dr. Abeer Muhammad Aljufair 4. The Psychometric properities of the online teaching competencies scale among faculty members at Umm Al-Qura University Mrs. Eptehal Zakaria Hafiz 5. Building a training program to develop the performance of kindergarten teachers and measuring its impact on developing the Speaking skills of kindergarten children for the Republic of Yemen Mrs. Zakiah Mohammed Ali Al-Jamrah 6. Educational Implications of the Winter Season’s Provisions in the Light of Islamic Education Mrs. Mashael Raja Alhizan , Mrs. Rasha Ghazi Matar , Mrs. Hanna Hamed Aljuhani , Mrs. Belqes Mohammed Ahmed Atya 7. The Orientation Towards Helping Others and its Relationship with Emotional Awareness among University Students. Mrs. Hanan Hussein Ibrahim Shaaban , Co-Prof. Iyad Grace Al-Shawareb 8. Psychological Hardiness and its Relation to Social Networking Sites Addiction among a Sample of Female Adolescents in Jeddah Mrs. Sara Naif Mansoor , Co-Prof. Radyah Mohammed Hamidaddin